Exploring architectural knowledge in water sensitive design - Bhikha, Preetya (School of Architecture, Planning and Geomatics, 2018)
Across the academic sphere, much research has been conducted into the development of water-sensitive elements to address issues around urban water management. However, these elements are commonly investigated in isolation, with little consideration for initiatives from other disciplines that may support their success. This research aims to demonstrate the value that an architect may bring in incorporating ideas drawn from various disciplines to create a water- sensitive design solution with multiple ecosystem benefits, taking into account the human experience of space and place-making. In doing so, the design demonstrates that a water-sensitive building is aesthetically pleasing, viable and achievable. The feasibility of water-sensitive designs has been noted as a focus area by the South African Water Research Commission; one which is particularly pertinent in our present water-scarce environment in South Africa. This applied study is based on a previous Master of Architecture (Professional) dissertation building design, which is used as the unit of analysis. The building focuses on restoring the quality of water in the Liesbeek River in Cape Town using passive filtration methods. The objective of this study is to gain new insights into the design process and planning of water-sensitive architectural buildings, which assists in understanding when collaborating across disciplines. The research is guided by Deep Ecology, phenomenology and Ecological Urbanism. Research by Design is used as the method of the study, in which different design iterations based on the raw data of the original building are investigated and analysed, as well as evaluated by specialists from various disciplines in order to create a best-fit design solution. The revised building takes into account the practical, site-specific and architectural qualities of a water-sensitive design to create a people-centred building that incorporates ecological and engineering demands in greater detail. Key outcomes of the study include a typical design process for a WSAD and architectural guidelines for water-sensitive buildings, grounded in the diverse values of water and its relationship to people and nature. The dissertation aims to contribute to the academic discourse around water-sensitive design. Further, the guidelines developed may be used to inform the design of conventional buildings.